Effect of Hemodialysis on Anterior Chamber Angle Measured by Anterior Segment Optical Coherence Tomography. (14th August 2019) - Shin, Yong Un; Kim, Ji Hong; Cho, Heeyoon; Kim, Dae Sung; Yi, Joo-Hark; Han, Sang-Woong; Seong, Mincheol
Abstract : Purpose . To investigate the effect of hemodialysis (HD) on the anterior chamber angle by anterior segment optical coherence tomography (ASOCT) and other ophthalmologic parameters in patients with end-stage kidney disease (ESKD). Methods . A prospective observational study was performed on 20 patients who underwent HD for ESKD. Anterior chamber angle images were obtained by 16 mm line scan of ASOCT. The angle opening distance (AOD) and the trabecular-iris space area (TISA) were determined using the ImageJ program. Additional 12 mm horizontal and 9 mm vertical wide-field scans centered on the posterior pole were performed for the measurement of peripapillary retinal nerve fiber layer (pRNFL) thickness and macular ganglion cell-inner plexiform layer (mGCIPL) thickness. Changes in intraocular pressure (IOP), AOD, TISA, pRNFL thickness, and mGCIPL thickness before and after HD were statistically analyzed. Results . The IOP decreased significantly from 17.5 ± 3.4 before HD to 16.2 ± 2.3 after HD (P = 0.017 ). There was a statistically significant decrease in AOD 750 and TISA 750 (P = 0.005 andP = 0.007, respectively). AOD 500 and TISA 500 also decreased, which was almost statistically significant (P = 0.061 andP = 0.081, respectively). Mean pRNFL thickness and mGCIPL thickness did not show significant change after HD. Conclusion . We observed a significant decrease in IOP and anterior chamber angle measurements after HD. Our study suggests that HD can influence the anterior segment structure of eyes.